Yuan-Zhi decoction in the treatment of Alzheimer’s disease: An integrated approach based on chemical profiling, network pharmacology, molecular docking and experimental evaluation - Wu, Qiong; Li, Xiang; Jiang, Xiao-Wen; Yao, Dong; Zhou, Li-Jun; Xu, Zi-Hua; Wang, Nan; Zhao, Qing-Chun; Zhang, Zhou (Frontiers in Pharmacology, 2022)
Yuan-Zhi Decoction (YZD) is a classic formula in traditional Chinese medicine with demonstrated beneficial effects in Alzheimer’s disease (AD). Combining liquid chromatography/mass spectrometry and database searches we identified 27 unique chemical components of YZD. Network pharmacology analysis and molecular docking models detected 34 cellular targets involving 26 molecular pathways that are potentially affected by these compounds. In behavioral studies, using the Morris water maze test (MWM) APP/PS1 transgenic mice showed measurably improved spatial orientation and memory after the administration of YZD, demonstrating the benefits of this traditional formula in a transgenic mouse model of AD. Finally, we utilized Western blotting to evaluate whether YZD affected the molecular pathways predicted in silico. Administration of YZD decreased BACE1 and beta-amyloid levels, up-regulated the PI3K and p-AKT/AKT, while down-regulating p-GSK-3β/GSK-3β, confirming that predicted changes do occur in vitro. This study provides scientific support for the clinical use of YZD and justifies further investigations into its effects while demonstrating that the network pharmacology approach could be a powerful tool in studying the mechanisms of action of traditional Chinese medicines.